Pendidikan Politik Pemilih Muda Dalam Pemilihan Kepala Desa Serentak di Kabupaten Bandung 2019 - Kurniasih, Dewi (Indonesian Community Service and Empowerment Journal (IComSE), 2020)
ABSTRACT Young voters in the head of village election simultaneously 2019’s are a new generation of voters who have different characteristics and characters, backgrounds, experiences and challenges from the previous generation of voters. Most of them come from among students, have good economic status, and generally live in urban or surrounding areas. They are very open to learning new, critical and independent things. The contribution of young voters in the field of village politics is based on the role of youth as controlling agents. Young voters, especially in villages, can provide insight to village communities regarding the head of village elections so that the community can actively participate in village head elections in order to minimize abstentions. The role of political education for young voters is very important to be implemented in achieving a high level of success in the head of village election simultaneously in Bandung Regency in 2019. Key words: political education, young voters, the head of village election ABSTRAK Pemilih muda pada pilkades serentak di Kabupaten Bandung tahun 2019 adalah generasi baru pemilih yang memiliki sifat dan karakter, latar belakang, pengalaman dan tantangan yang berbeda dengan para pemilih generasi sebelumnya. Sebagian besar di antara mereka berasal dari kalangan pelajar, berstatus ekonomi baik, dan pada umumnya tinggal di kawasan perkotaan atau sekitarnya. Mereka sangat terbuka untuk mempelajari hal-hal yang baru, kritis dan juga mandiri. Kontribusi pemilih muda dalam bidang politik desa berlandaskan atas peran pemuda sebagai Agen controlling. Pemilih muda terutama di desa dapat memberikan wawasan kepada masyarakat desa terkait pemilihan kepala desa agar masyarakat dapat turut aktif berpartisipasi dalam pemilihan kepala desa guna meminimalisir golput. Peran pendidikan politik bagi pemilih muda sangat penting untuk dilaksanakan dalam mencapai tingkat kesuksesan yang tinggi pada pilkades serentak di Kabupaten Bandung Tahun 2019. Kata kunci: pendidikan politik, pemilih muda, pemilihan kepala desa